Radially aligned hierarchical columnar structure as a cathode material for high energy density sodium-ion batteries - Hwang, Jang-Yeon; Oh, Seung-Min; Myung, Seung-Taek; Chung, Kyung Yoon; Belharouak, Ilias; Sun, Yang-Kook (NATURE PUBLISHING GROUP, 2015)
Delivery of high capacity with good retention is a challenge in developing cathodes for rechargeable sodium-ion batteries. Here we present a radially aligned hierarchical columnar structure in spherical particles with varied chemical composition from the inner end (Na[Ni0.75Co0.02Mn0.23]O-2) to the outer end (Na[Ni0.58Co0.06Mn0.36]O-2) of the structure. With this cathode material, we show that an electrochemical reaction based on Ni2+/3+/4+ is readily available to deliver a discharge capacity of 157 mAh (g-oxide)(-1) (15 mA g(-1)), a capacity retention of 80% (125 mAh g(-1)) during 300 cycles in combination with a hard carbon anode, and a rate capability of 132.6 mAh g(-1) (1,500 mA g(-1), 10 degrees C-rate). The cathode also exhibits good temperature performance even at -20 degrees C. These results originate from rather unique chemistry of the cathode material, which enables the Ni redox reaction and minimizes the surface area contacting corrosive electrolyte.
Keywords: LOW-TEMPERATURE PERFORMANCE; HIGH-CAPACITY; ELECTROCHEMICAL INTERCALATION; ELECTRODE PERFORMANCE; POSITIVE ELECTRODE; NAXCOO2; P2-TYPE; NACRO2; ANODE; POWER